APLIKASI PEMESANAN TIKET WISATA PANTAI MENGANTI BERBASIS MOBILE DENGAN INTERGRASI PEMBAYARAN DIGITAL - Setyawan, Feri; Anggara, Afwan (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Menganti Beach, known for its scenery, is one of the popular tourist destinations in Kebumen Regency. Currently, the process of ordering and paying for tourist tickets is still done manually, causing long queues at the counter and hampering operational efficiency. Therefore, a mobile-based tourist ticket ordering application with digital payment integration is expected to help managers in the ticket ordering and payment process to be more efficient in terms of time so as not to cause long queues. Otherwise, the long queues at the counter will continue, resulting in an unpleasant tourist experience and decreased interest in tourist visits, which ultimately has a negative impact on tourist income. To overcome this problem, the study designed and created a mobile-based application that includes ticket ordering, online payment, and ticket checking features. By using the Waterfall method, it is expected that the steps taken include problem analysis, data collection through surveys and interviews, system design, implementation, testing, and application maintenance to ensure all features are functioning properly. Interim results show that this application can help tourism managers improve the efficiency of the booking and payment process time, thereby providing a better experience for visitors.